A Thousand Swings Banua's : Baayun Maulid Tradition as Sustainable Religious Tourism at the Sacred Banua Halat Mosque - Haura Nabila; Rahman Hakim, Arif (Multikultural: Jurnal Ilmu Sosial, 2025)
This study examines A Thousand Swings Banua’s: Baayun Maulid Tradition as Sustainable Religious Tourism at the Sacred Banua Halat Mosque. With This study examines "Banua of a Thousand Swings: The Baayun Maulid Tradition as a Sustainable Religious Tourism Event at the Keramat Mosque of Banua Halat." Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation. Two theoretical frameworks were employed: Colin Michael Hall's Cultural Sustainability Theory and Robert K. Merton's Structural Functionalism Theory. The findings reveal that the Baayun Maulid tradition in Banua Halat Kiri is a well-preserved cultural heritage managed by the local community. It has unique appeal, attracting numerous participants and sparking curiosity about the tradition. Beyond being a cultural practice, it is also framed as a religious tourism event. For the sustainability of this tourism initiative, it is essential to manage both the cultural sustainability aspects and the social functions or impacts effectivelya qualitative descriptive approach, data were collected through observation, interviews and documentation. Using 2 theories, namely Colin Michael Hall's Cultural Sustainability Theory and Robert K. Merton's Structural Functional Theory. The results of this study reveal that the Baayun Maulid Tradition in Banua Halat Kiri Village is one of the traditional heritages that is still well managed by its community and has its own appeal with the many participants who follow the tradition so that it makes other people's curiosity even higher with the tradition and not just the implementation of the tradition but also a tradition that is packaged as religious tourism. Aspects of sustainability and existing functions or impacts must be managed simultaneously well, so that the tourism can continue.